Improving the results of triple jump exercise using image and video media - Simanjuntak, Victor; Maksum, Hendri (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The purpose of the study was to determine the effectiveness of triple jump exercises using pictures and videos. This research uses the sports action method adopted from the Class Action Research approach. The research subjects are triple jump athletes at PON XX West Kalimantan in 2021, totaling 10 athletes. Data analysis using data reduction in the form of image and video stimulation, then there is data presentation and conclusions from observations through 2 cycles using percentage techniques. The results obtained are overall from the initial cycle before the treatment obtained an average result of 46.42%, then the average value after the second treatment got the final result of 76.42%. It means that there is a percentage increase from the initial value of 30.00%. The conclusion that can be drawn is that the use of image and video media can provide higher motivation to athletes in training and at the same time can improve training results, both technical quality and achievement in jumps. Then it is expected to be input for coaches and athletes to determine the appropriate training method.